Extended Glasgow Outcome Scale correlates with bispectral index in traumatic brain injury patients who underwent craniotomy - Mahadewa, Tjokorda Gde Bagus (Open Access Emerg Med, 2018)
BACKGROUND: Assessing consciousness in traumatic brain injury is important because it also determines the treatment option, which will influence patients’ outcome. A tool used to objectively assess consciousness level is the bispectral index (BIS) monitor, which was originally designed to monitor the depth of anesthesia. Glasgow Outcome Scale-Extended (GOS-E) provides a measuring tool to assess traumatic brain injury (TBI) outcome. The goal of this study was to assess the correlation between GOS-E scores with BIS values in patients with TBI who underwent craniotomy. PATIENTS AND METHODS: A total of 68 patients admitted to the emergency department with decreased consciousness due to TBI who underwent craniotomy were included in the study. BIS value was measured upon admission, then GOS-E score was determined 6 months after the incident took place. Spearman’s correlation coefficient was used to assess the correlation between GOS-E score and BIS value. RESULTS: In 68 patients, the GOS-E score was found to have a strong correlation (r =0.921, p<0.01) with BIS values. From this study, the formula to estimate GOS-E score based on BIS value upon admission stands as: GOS-E =0.19 (BIS) – 8.31. CONCLUSION: This study found that there is a strong correlation between GOS-E score and BIS value. These findings suggest that BIS scores upon admission may be used to predict the outcomes in patients with TBI. However, the wide distribution of BIS values for each GOS-E score may limit the use of BIS scores in accurately predicting GOS-E scores.